Hydrographic parameters and sedimentary characteristics under the influence of glacial derived meltwater in the Kongsfjorden-Krossfjorden fjord system, Svalbard - Resmi Panikkaveetil; Anu Gopinath; B. Karthika; T. Divya David; K. Anoop Krishnan (Polar Science, 2026)

Data-driven interpretation and optimization of crimson red dye adsorption using spirulina-derived hydrochar–CuO nanocomposites - B. Subha; S. Murugeshwari; B. Senthil Rathi; J. Divya; E. Krithya (Biomass and Bioenergy, 2026)

A Comprehensive Study on the Chemical, Biological, and Environmental Factors Shaping the Medicinal Value of Euphorbia hirta - J. B. Reshmi; P. S. Abitha; P. C. Divya; S. Grace Victoria; V. N. Meena Devi (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2026)

Health challenges in silkworm host plants: current knowledge and sustainable management approaches - Shreenath Y. S.; Divya Rajawat; Harendra Yadav; Madhu G. S.; Hanamant Gadad; Jaya Minz; Khanak Sharma; N. B. Chowdary (Tropical Plant Pathology, 2026)

Meeting Child and Adult Care Food Program Meal Patterns May Not Ensure Healthier Snack Menus in Family Child Care Homes - Progati Bakshi; Susan B. Sisson; Divya Patel; Alicia L. Salvatore; Saima Hasnin (Journal of Nutrition Education and Behavior, 2026)

Plant-Mediated CuO Nanoparticles for Reactive Orange Dye Adsorption: Experimental study and Machine Learning-Assisted Optimization - S. Murugeshwari; Madhan Gunasekaran; B. Senthil Rathi; R. M. Saravana Kumar; J. Divya (Water, Air, & Soil Pollution, 2026)

Intraspecific Variation of Edwardsiella anguillarum From Non‐Anguillid Fish From Varied Geographic Origins - Abigail R. Armwood; Divya Rose; Geoffrey C. Waldbieser; Ethan Woodyard; Bradley M. Richardson; Esteban Soto; Cynthia B. Stine; Cynthia C. Ware; Paola Barato; Alvin C. Camus; Matt J. Griffin (Journal of Fish Diseases, 2026)
Edwardsiella anguillarum is a gram‐negative bacterium, synonymous with previously described atypical, fish‐pathogenic Edwardsiella tarda . Originally described from eels in 2015, E. anguillarum is an important global fish pathogen, particularly in tilapia. This study describes intraspecific phenotypic and genotypic variability among 17 E. anguillarum isolates from non‐anguillid fish hosts and varied geographic origins. Isolates demonstrated similar biochemical characteristics, with slight variation in motility and hydrogen sulfide production. Genomic relatedness among isolates was analysed with repetitive extragenic palindromic sequence‐based PCR (rep‐PCR) and multilocus sequence analysis (MLSA). Rep‐PCR with the ERIC II primer set revealed two distinct genetic clusters, while amplification strategies utilising the GTG 5 , BOX or ERIC I&II primer sets yielded more uniform profiles. While rep‐PCR deemed the isolates largely clonal, MLSA schemes using reference genes from published Edwardsiella MLSA studies revealed E. anguillarum isolates formed five discrete phylogroups. A unique, ~91.5 kB plasmid was identified in Costa Rican and Colombian isolates, associated with conjugative and transposable elements, plasmid mobilisation, and adhesion; however, no plasmid mediated antibiotic resistance genes were identified. This study provides insight into genetic diversity among E. anguillarum isolates from different hosts and geographic regions, identifying an optimal MLSA scheme from previous reports applicable to E. anguillarum isolates.

Prebreeding using untapped rice genetic resources: linking the gap between biodiversity and crop improvement - Santhosh Venna; Divya Balakrishnan; P. K. Singh; B. Arun; Suneetha Kota; S. Amurutha Rao; Naresh Kumar Sahu; S.V. SaiPrasad; R. M. Sundaram (Journal of Crop Science and Biotechnology, 2026)

Critical habitats for sharks and rays in Asia remain largely unprotected - Adriana Gonzalez-Pestana; Peter M. Kyne; Emiliano García-Rodríguez; Ryan Charles; Vanessa Bettcher Brito; Asia O. Armstrong; Amanda Batlle-Morera; Marta D. Palacios; Christoph A. Rohner; Giuseppe Notarbartolo di Sciara; Jo Marie V. Acebes; Serena Adam; et al. (Biodiversity and Conservation, 2026)
The Asia region harbors exceptional chondrichthyan (shark, ray, and chimaera) diversity but faces intense fishing pressure. The Important Shark and Ray Areas (ISRA) process provides a collaborative, evidence-based framework to identify critical habitats and inform spatial management. We assessed ISRAs across the Bay of Bengal, Southeast Asia, and the Northwest Pacific to characterize their extent, ecological significance, and conservation relevance. We delineated 122 ISRAs spanning ~ 1 million km 2 (~ 3% of the region) across 12 jurisdictions and international waters, encompassing habitats for 121 species (~ 30% of Asia’s chondrichthyans), 76% of which are threatened. Depleted taxa (e.g., giant guitarfishes, Glaucostegidae) were represented, but charismatic megafauna (e.g., Whale Shark Rhincodon typus ) were overrepresented. In contrast, deepwater and freshwater species were underrepresented. Reproductive Areas were the most common ISRA sub-criterion applied (52% of ISRAs), largely in nearshore zones, while areas for range-restricted species were less frequently (18%) identified. Twelve ISRAs overlapped with biodiversity hotspots, including seven in areas of high overall chondrichthyan species richness and five in areas of high range-restricted species richness. Citizen science was the predominant research method used to delineate ISRAs, while fisheries data were underused despite the region’s major fisheries footprint. Geographic coverage was uneven: Indonesia held the most ISRAs (n = 40; 71.7% of ISRA coverage) while eight jurisdictions (e.g., Viet Nam, China, Republic of Korea) lacked ISRAs due to data gaps. Protection shortfalls are stark: MPAs cover

Happy Healthy Homes Virtual Intervention Improved Rural Family Child Care Home Provider Mealtimes: Partial and Sustained Effects - Divya Patel; Dipti A. Dev; Steven Pan; Bethany Williams; Alicia L. Salvatore; Susan B. Sisson (Journal of Nutrition Education and Behavior, 2026)

Biophysical basis and morphological traits conferring resistance to yellow stem borer, Scirpophaga incertulas (walker) in land races of rice (Oryza sativa L.) - Divya D. Mallesh; Vijaykumar Lingaraj; B. Shivanna; Reddy C. N. Lakshminarayana; M. S. Kitturmath; H. R. Raveendra; K. R. Ashoka (International Journal of Tropical Insect Science, 2026)

Stress Resilience in Tuber Crops: A Closer View on Genome Editing and Molecular Approaches - Pandian Rajendran; Krishnagowdu Saravanan; B. Jagadhesan; R. Ramesh; Divya Bharathi; Pavithra Suryakumar; Nitin Sharma; Yogesh Yele; Ashish Marate; Niranjan Prasad; N. D. Vinay; Palaiyur Nanjappan Sivalingam; et al. (Journal of Plant Growth Regulation, 2026)

Understanding the persistence of rice residue burning in northwestern India: A mixed methods approach - Divya Solomon; Andrew McDonald; Christopher B Barrett; Prakashan Chellattan Veettil; Buta Singh Dhillon (Agricultural Systems, 2026)

Comparison of clinical, radiological and outcome parameters in patients with progressive multifocal leukoencephalopathy (PML) with and without HIV infection: a cohort study - Farsana Mustafa; Anuj Ajayababu; Ajay Garg; Megha Brijwal; Divyani Garg; Manish Soneja; Aashish Choudhary; Lalit Dar; Shariq A. Shah; Venugopalan Y Vishnu; Animesh Ray; Neeraj Nischal; et al. (Journal of NeuroVirology, 2025)

Genetic Diversity and Population Structure Analysis in Avocado (Persea americana) Accessions of India - B. M. Muralidhara; T. Sakthivel; D. C. Lakshmana Reddy; G. Karunakaran; V. Venkatravanappa; Siddanna Savadi; Divya Vani Vaka; Ponnam Naresh; K. S. Shivashankara; R. Venugopalan; M. K. Honnabyraiah (Agricultural Research, 2025)

Isolation and characterization of xyloglucan endotransglucosylase/hydrolase (XET/XTH) provide insights on the functional evolution of XET family proteins in ginger (Zingiber officinale Roscoe) - Arshya Devi; Divya P. Syamaladevi; B. Mekha; K. S. Nehamol; I. P. Vijesh Kumar; T. E. Sheeja; D. Prasad (Genetic Resources and Crop Evolution, 2025)

Harnessing inter-subspecific genetic variability for hybrid rice improvement: analysis of genetic diversity, heterosis, and combining ability - K. Sruthi; K. B. Eswari; Ch. Damodar Raju; M. Sheshu Madhav; A. Dhandapani; M. Bala Satya Sree; K. Srikrishna Latha; P. Koteswararao; M. Sadath Ali; Divya Balakrishnan; P. Senguttuvel; Revathi Ponnuswamy; et al. (Euphytica, 2025)

Deciphering mating type and population genetic landscape of Magnaporthe population adapted to millets and rice in blast hotspots of India - K. B. Palanna; Gutha Venkata Ramesh; Prasanna S. Koti; H. D. Vinaykumar; Divya Bhandhari; H. R. Raveendra; T. S. S. K. Patro; T. V. Krishna; T. E. Nagaraja; R. Madhusudhana; C. Tara Satyavathi (Archives of Microbiology, 2025)

Gracilarioside A, New Glycolipid and other cytotoxic constituents from red algae Gracilaria edulis - Kotta Ramulu; Solipeta Divya Reddy; Bandi Siva; Penta Poornima; Lakkakula Satish; B. Sridhar; Katragadda Suresh Babu (Phytochemistry Letters, 2025)

Optimized biodiesel production from Java olive seeds using a novel magnetic nanobiocatalyst and advanced optimization techniques - L.R. Monisha Miriam; Ajith J. Kings; Jain B. Marshel; R. Edwin Raj; S. Indran; D. Divya (Biomass and Bioenergy, 2025)

Systematic revision of the genus Orchidasma Looss, 1900 and description of Orchidasma orchilobata n. sp. from the loggerhead Caretta caretta (L.) and Kemp’s ridley Lepidochelys kempii (Garman) turtles - Thomas G. Rosser; Aiden Meaux; Ethan T. Woodyard; Justin M. Stilwell; Bradley M. Richardson; Logan R. S. Robison; Jill B. Hudnall; Kaylin McNulty; Jonah A. Nguyen; Divya Rose; Debra Moore; Beth Peterman; et al. (Systematic Parasitology, 2025)

Separating Historical Catches Among Pygmy Blue Whale Populations Using Recent Song Detections - Trevor A. Branch; Cole C. Monnahan; Emmanuelle C. Leroy; Fannie W. Shabangu; Ana Širović; Salvatore Cerchio; Suaad Al Harthi; Cherry Allison; Naysa Balcázar Cabrera; Dawn R. Barlow; Susannah V. Calderan; Michael C. Double; et al. (Marine Mammal Science, 2025)
In the Southern Hemisphere and northern Indian Ocean, there are at least five populations of pygmy blue whales, Balaenoptera musculus brevicauda , residing in the Northwest Indian Ocean (NWIO, Oman), central Indian Ocean (CIO, Sri Lanka), Southwest Indian Ocean (SWIO, Madagascar to Subantarctic), Southeast Indian Ocean (SEIO, Australia to Indonesia), and Southwest Pacific Ocean (SWPO, New Zealand). Each population produces a distinctive repeated song, but none have population assessments or reliable measures of historical whaling pressure. Here we created pygmy blue whale catch time series by removing Antarctic blue whale catches using length data and then fitting generalized additive models (based on latitude, longitude, and month) to contemporary song data (largely from 1995 to 2023) to allocate historical catches to the five populations. Most pygmy blue whale catches (97% of 12,207) were taken by Japanese and Soviet operations during 1959/1960 to 1971/1972, with the highest totals taken from the SWIO (6514), SEIO (2593), and CIO (2023), and lower catches from the NWIO (549) and SWPO (528). The resulting predicted annual catch assignments provide the first indication of the magnitude of whaling pressure on each population and are a key step toward assessing the status of these five pygmy blue whale populations.

Evaluation of Eclipta alba L. selections for higher biomass and bioactive compound - K. Hima Bindu; K. Keshav Rao; Shiva Kumar; B. Anil Kumar; R. M. Shalini; Priti Sonavane; K. S. Divya; S. Sujatha (Genetic Resources and Crop Evolution, 2025)

Climate Geoscience–Based Disaster Management in Healthcare Analysis by Markov Q-Transfer Adversarial with Cloud Computing - Jhade Srinivas; B. Rebecca; Kovvuri N Bhargavi; Velma Reddy Swetha; S. Spandana; Divya Priya Degala (Remote Sensing in Earth Systems Sciences, 2025)

Plant diversity and microbial interaction on soil carbon stock in the tropical homegardens: a nature-based solution to climate change - Athulya Tom; V. Divya Vijayan; T. K. Kunhamu; S. Sandeep; K. Surendra Gopal; V. Jamaludheen; B. R. Vishnu (Agroforestry Systems, 2025)

Novel Ti/rGO@ZnCr LDH derived MMO for photocatalytic conversion of atmospheric elements and organic pollutants into valuable resources - Prabagar Jijoe Samuel; Tenzin Thinley; Divya Vinod; Hosakote Shankara Anusha; Hemanth Vikram P R; Gurupadayya B M; Kotermane Mallikarjunappa Anilkumar; Manickam Selvaraj; Mohammed A. Assiri; Harikaranahalli Puttaiah Shivaraju (Journal of Environmental Chemical Engineering, 2024)

An evaluation of in utero polycyclic aromatic hydrocarbon exposure on the neonatal meconium microbiome - Divya Keerthy; Miranda J. Spratlen; Lingsheng Wen; Dwayne Seeram; Heekuk Park; Lehyla Calero; Anne-Catrin Uhlemann; Julie B. Herbstman (Environmental Research, 2024)

Remote Sensing–Based UAV Imaging in Heat Pattern Analysis Impact on Climate Change Detection Using Fuzzy Stacked Lasso Elastic-Net Model - M. Sailaja; M. Prema Kumar; B. Swarna Jyothi; G. L. Narasamba Vanguri; S. Manjula; D. Divya Priya (Remote Sensing in Earth Systems Sciences, 2024)

Geospatial assessment of agroforestry land use systems using very high-resolution satellite images and artificial intelligence - Shivam Trivedi; P. V. Vinod; B. Chandrasekaran; M. K. Nagashree; S. Rama Subramoniam; V. B. Manjula; Amrita Singh; J. K. Mani; Arun S. Suryavanshi; Sushilkumar B. Rehpade; Akash Goyal; N. R. Shankar Ram; et al. (Agroforestry Systems, 2024)

Head Impact Kinematics and Brain Tissue Strains in High School Lacrosse - Declan A. Patton; Colin M. Huber; Divya Jain; Svein Kleiven; Zhou Zhou; Christina L. Master; Kristy B. Arbogast (Annals of Biomedical Engineering, 2024)

Female Collegiate Athletes’ Concussion Characteristics and Recovery Patterns: A Report from the NCAA-DoD CARE Consortium - Landon B. Lempke; Jaclyn B. Caccese; Reid A. Syrydiuk; Thomas A. Buckley; Sara P. D. Chrisman; James R. Clugston; James T. Eckner; Elsa Ermer; Carrie Esopenko; Divya Jain; Louise A. Kelly; Allyssa K. Memmini; et al. (Annals of Biomedical Engineering, 2024)

Initial Mild Traumatic Brain Injury Characteristics and Recovery Patterns Among Females Across the United States Military Service Academies: A Report from the NCAA-DoD CARE Consortium - Landon B. Lempke; Elsa Ermer; Adrian J. Boltz; Jaclyn Caccese; Thomas A. Buckley; Kenneth L. Cameron; Sara P. D. Chrisman; Christopher D’Lauro; James T. Eckner; Carrie Esopenko; Tamerah N. Hunt; Divya Jain; et al. (Annals of Biomedical Engineering, 2024)

Quantifying abnormal writing kinematics in writer’s cramp using a novel software platform - Kavadisseril Vivekanandan Vysakha; Vineeth Radhakrishnan; Praveen James; B. Suresh Kumar; Ashish Anand Susvirkar; Gangadhara Sarma; Ajith Cherian; K. P. Divya; Syam Krishnan Nair; Asha Kishore (Acta Neurologica Belgica, 2024)

A Comprehensive Insight into the Pharmaceutical Potential of Saussurea obvallata - Nabarun Mukhopadhyay; Divya Jain; Anjali Tripathi; Amith Kumar B; Pranav Bhaskar (Current Pharmacology Reports, 2024)

Genomic patterns of selection in morphometric traits across diverse Indian cattle breeds - Divya Rajawat; Sonali Sonejita Nayak; Karan Jain; Anurodh Sharma; Subhashree Parida; Sarada Prasanna Sahoo; Bharat Bhushan; D. B. Patil; Triveni Dutt; Manjit Panigrahi (Mammalian Genome, 2024)

Efficacy of biological agent Lecanicillium lecanii for the management of coffee leaf rust in India - Divya K. Das; Santoshreddy Machenahalli; Madhu S. Giri; Ranjini A. P; N. Suryaprakash Rao; M. B. Shivanna (Indian Phytopathology, 2024)

Microbiota of Saliva: A Non-invasive Diagnostic Tool - Dasharath B. Shinde; Jayashri G. Mahore; Prabhanjan S. Giram; Shaktikumar L. Singh; Aditi Sharda; Divya Choyan; Shubham Musale (Indian Journal of Microbiology, 2024)

Stability analysis and genetic mapping for yield traits of rice wild introgression lines - N. P. S. De Silva; P. Magudeeswari; Divya Balakrishnan; V. Gouri Shankar; B. Kavitha; A. Krishnamraju; P. Prashanthi; K. Vaibhav; D. S. Chary; S. N. C. V. L. Pushpavalli; Sarla Neelamraju (Cereal Research Communications, 2024)

Metal organic frameworks: Building blocks for a greener future - Dhamodharan Duraisami; Mamdouh Ahmed Al-Harthi; Ramya B; Divya Baskaran; Elakkiya M; Abdullah Bafaqeer (Journal of Cleaner Production, 2024)

Meta-QTL analysis in wheat: progress, challenges and opportunities - Divya Sharma; Anita Kumari; Priya Sharma; Anupma Singh; Anshu Sharma; Zahoor Ahmad Mir; Uttam Kumar; Sofora Jan; M. Parthiban; Reyazul Rouf Mir; Pradeep Bhati; Anjan Kumar Pradhan; et al. (Theoretical and Applied Genetics, 2023)

Comprehensive selection signature analyses in dairy cattle exploiting purebred and crossbred genomic data - Sonali Sonejita Nayak; Manjit Panigrahi; Divya Rajawat; Kanika Ghildiyal; Anurodh Sharma; Subhashree Parida; Bharat Bhushan; B. P. Mishra; Triveni Dutt (Mammalian Genome, 2023)

Drought stress in maize: stress perception to molecular response and strategies for its improvement - Ashutosh Singh; Himanshu Pandey; Saurabh Pandey; Dalpat Lal; Divya Chauhan; Aparna; Suresh H. Antre; Santhosh B; Amarjeet Kumar (Functional & Integrative Genomics, 2023)

Toxicity prediction and analysis of flavonoid apigenin as a histone deacetylase inhibitor: an in-silico approach - N. Divya Rajaselvi; M. D. Jida; Devu B. Nair; S. Sujith; Nisaath Beegum; A. R. Nisha (In Silico Pharmacology, 2023)

A comprehensive health effects assessment of the use of sanitizers and disinfectants during COVID-19 pandemic: a global survey - Fallah Hashemi; Lori Hoepner; Farahnaz Soleimani Hamidinejad; Daniela Haluza; Sima Afrashteh; Alireza Abbasi; Elma Omeragić; Belma Imamović; Narin A. Rasheed; Taqi M. J. Taher; Fitri Kurniasari; Dhuha Youssef Wazqar; et al. (Environmental Science and Pollution Research, 2023)

Improvement of small seed for big nutritional feed - P. B. Kavi Kishor; S. Anil Kumar; Jalaja Naravula; P. Hima Kumari; Divya Kummari; Rajasheker Guddimalli; Sujatha Edupuganti; Appa Rao Karumanchi; Perumal Venkatachalam; Prashanth Suravajhala; Rathnagiri Polavarapu (Physiology and Molecular Biology of Plants, 2021)

Single gene variants causing deafness in Asian Indians - Inusha Panigrahi; Divya Kumari; B. N. Anil Kumar (Journal of Genetics, 2021)

Exploration of Heat Stress-Responsive Markers in Understanding Trait Associations in Wheat - P. B. Manjunatha; Nivedita Sinha; Hari Krishna; Divya Chauhan; Pawan Kumar; Ranjeet R. Kumar; Neelu Jain; P. K. Singh; G. P. Singh (Journal of Plant Biology, 2021)

Renoprotective effect of tectorigenin glycosides isolated from Iris spuria L. (Zeal) against hyperoxaluria and hyperglycemia in NRK-49Fcells - Ganesan Divya; Abhishek Albert; Abdel Nasser B. Singab; Iriny M. Ayoub; Eman Al-Sayed; Eldho Paul; Kumarriah Manoharan; Luciano Saso; Govindan Sadasivam Selvam (Natural Product Research, 2021)

Experimental Evaluation of Seaweeds Liquid Extracts as an Alternative Culture Medium on the Growth and Proximate Composition of Picochlorum maculatum - S. Bharathi; S. Dinesh Kumar; S. Sekar; P. Santhanam; M. Divya; N. Krishnaveni; M. Pragnya; B. Dhanalakshmi (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2021)

An update and perspectives on the use of promoters in plant genetic engineering - Divya Kummari; Sudhakar Reddy Palakolanu; P B Kavi Kishor; Pooja Bhatnagar-Mathur; Prasanth Singam; Vincent Vadez; Kiran K Sharma (Journal of Biosciences, 2020)

RECK and TIMP-2 mediate inhibition of MMP-2 and MMP-9 by Annona muricata - G Drishya; Jyotsna Nambiar; Sanu K Shaji; Muralidharan Vanuopadath; A Achuthan; Abishek Kumar; Ashna Alias; Ayesha Sherif; Catherine Joseph; P Divya; Damu Sunil Kumar; Chinchu Bose; et al. (Journal of Biosciences, 2020)

Epigenetics and epigenomics: underlying mechanisms, relevance, and implications in crop improvement - Gaurav Agarwal; Himabindu Kudapa; Abirami Ramalingam; Divya Choudhary; Pallavi Sinha; Vanika Garg; Vikas K Singh; Gunvant B Patil; Manish K Pandey; Henry T Nguyen; Baozhu Guo; Ramanjulu Sunkar; et al. (Functional & Integrative Genomics, 2020)

Head Impact Sensor Studies In Sports: A Systematic Review Of Exposure Confirmation Methods - Declan A. Patton; Colin M. Huber; Divya Jain; Rachel K. Myers; Catherine C. McDonald; Susan S. Margulies; Christina L. Master; Kristy B. Arbogast (Annals of Biomedical Engineering, 2020)

Evaluation of genetic diversity of parental lines for development of heterotic groups in hybrid rice (Oryza sativa L.) - K. Sruthi; B. Divya; P. Senguttuvel; P. Revathi; K. B. Kemparaju; P. Koteswararao; R. M. Sundaram; Vikram Jeet Singh; E. Ranjith Kumar; Prolay Kumar Bhowmick; K. K. Vinod; S. Gopala Krishnan; et al. (Journal of Plant Biochemistry and Biotechnology, 2020)

Sheath blight and drought stress management in rice (Oryza sativa) through Trichoderma spp. - Divya Mishra; Rahul Singh Rajput; Najam Waris Zaidi; H. B. Singh (Indian Phytopathology, 2020)

Isolation and functional characterization of three abiotic stress-inducible (Apx, Dhn and Hsc70) promoters from pearl millet (Pennisetum glaucum L.) - Kummari Divya; P. B. Kavi Kishor; Pooja Bhatnagar-Mathur; Prashanth Singam; Kiran K. Sharma; Vincent Vadez; Palakolanu Sudhakar Reddy (Molecular Biology Reports, 2019)

Seasonal variation in expression pattern of genes in irrigated and water stressed transcriptomes of Zea mays Z59 - B. Divya Bhanu; Kandasamy Ulaganathan; Arun K. Shanker (Journal of Plant Biochemistry and Biotechnology, 2019)

Genetic population structure of a highly migratory Hilsa Shad, Tenualosa ilisha, in three river systems, inferred from four mitochondrial genes analysis - Vindhya Mohindra; B. K. Divya; Rajesh Kumar; Rajeev K. Singh; Arvind Kumar Dwivedi; Sangeeta Mandal; Prachi Masih; Kuldeep K. Lal; J. K. Jena (Environmental Biology of Fishes, 2019)

Genomic characterisation of Cuiaba and Charleville viruses: arboviruses (family Rhabdoviridae, genus Sripuvirus) infecting reptiles and amphibians - Nikos Vasilakis; Robert B. Tesh; Steven G. Widen; Divya Mirchandani; Peter J. Walker (Virus Genes, 2019)

Muscle transcriptome resource for growth, lipid metabolism and immune system in Hilsa shad, Tenualosa ilisha - B. K. Divya; Vindhya Mohindra; Rajeev K. Singh; Prabhaker Yadav; Prachi Masih; J. K. Jena (Genes & Genomics, 2019)

Antioxidant activity of phenolic compounds from extracts of Eucalyptus globulus and Melaleuca styphelioides and their protective role on D-glucose-induced hyperglycemic stress and oxalate stress in NRK-49Fcells - Divya Ganesan; Eman Al-Sayed; Abhishek Albert; Eldho Paul; Abdel Nasser B. Singab; Selvam Govindan Sadasivam; Luciano Saso (Natural Product Research, 2018)

Serum Mortalin Correlated with α-Synuclein as Serum Markers in Parkinson’s Disease: A Pilot Study - Amrendra Pratap Singh; Teena Bajaj; Divya Gupta; Sundararajan Baskar Singh; Avinash Chakrawarty; Vinay Goyal; Aparajit B. Dey; Sharmistha Dey (NeuroMolecular Medicine, 2018)

An integrated geotechnical database and GIS for 3D subsurface modelling: Application to Chennai City, India - Divya Priya B.; G. R. Dodagoudar (Applied Geomatics, 2018)

Estimation of Cd, Pb and flame retardants in electric mosquito bat using EDXRF, ICP-OES, AAS and GC–MS - B. Divya; S. Harish; K. Ramaswamy; M. Kishorebabu; N. Raju; R. Govindaiah; U. Rambabu; N. R. Munirathnam (International Journal of Environmental Science and Technology, 2017)

Electrophoretic Separation of Humic Acids Isolated from Tropical Soils Through Modified Denaturing Polyacrylamide Gel Electrophoresis - Divya Pandey; Abhijit Sarkar; S. B. Agrawal; Madhoolika Agrawal (Agricultural Research, 2017)

Modulation of digestive enzymes, GH, IGF-1 and IGF-2 genes in the teleost, Tilapia (Oreochromis mossambicus) by dietary curcumin - Sebastian J. Midhun; Damodaran Arun; Lincy Edatt; M. V. Sruthi; V. V. Thushara; Oommen V. Oommen; V. B. Sameer Kumar; Lekha Divya (Aquaculture International, 2016)

Gene interactions and genetics of blast resistance and yield attributes in rice (Oryza sativa L.) - B. DIVYA; A. BISWAS; S. ROBIN; R. RABINDRAN; A. JOHN JOEL (Journal of Genetics, 2014)

Drought stress responses in crops - Arun K. Shanker; M. Maheswari; S. K. Yadav; S. Desai; Divya Bhanu; Neha Bajaj Attal; B. Venkateswarlu (Functional & Integrative Genomics, 2014)

Resistance reaction of gene introgressed lines against rice blast (Pyricularia oryzae) disease - B. Divya; S. Robin; R. Rabindran; H. Manjunath; P. Valarmathi; A. John Joel (Australasian Plant Pathology, 2014)

Genetic analysis of a type IV pili-like locus in the archaeon Methanococcus maripaludis - Divya B. Nair; Kaoru Uchida; Shin-Ichi Aizawa; Ken F. Jarrell (Archives of Microbiology, 2014)

Constitutive expression of mustard annexin, AnnBj1 enhances abiotic stress tolerance and fiber quality in cotton under stress - Kesanakurti Divya; S. K. Jami; P. B. Kirti (Plant Molecular Biology, 2010)

Transgenic tobacco and peanut plants expressing a mustard defensin show resistance to fungal pathogens - T. Swathi Anuradha; K. Divya; S. K. Jami; P. B. Kirti (Plant Cell Reports, 2008)